Envolvimento de óxido nítrico e de canais de potássio dependentes de ATP no efeito protetor da amifostina sobre as alterações motoras funcionais e inflamatórias da cistite hemorrágica induzida por Ifosfamida - Mourão, Lívia Talita Cajaseiras (2012)
Hemorrhagic cystitis (HC) is an inflammatory event often associated with the use of oxazafosforins. We have demonstrated that amifostine (AMF) may prevent tissue damage caused by ifosfamide (IFO). Considering that IFO also changes the motor function of the lower urinary tract, the present study aimed to investigate whether AMF protects animals against IFO-related bladder dysfunction, and if this effect occurs through anitric oxide (NO) and ATP-sensitive potassium channels (KATP) dependent mechanism. Male Swiss mice (25-30g, n = 8) were given saline or IFO (400mg/kg, ip) to induce HC. Another group received, 30min before IFO, AMF (50mg/kg, sc), aminoguanidine (AMG, 50 mg/kg, ip), ODQ (2 mg/kg, po) or glibenclamide (GLI, 10 mg/kg, ip ). Other groups received 30min before AMF, L-arginine (L-ARG, 600 mg/kg, ip), ODQ or diazoxide (DIAZ, 2mg/kg ip). In another experimental setting, the groups that received AMG were pretreated with L-arginine and those receiving GLI were pretreated with diazoxide each drug administered at intervals of 30 min. Bladder wet weight (BWW) and macroscopic and histopathological parameterswere analyzed 12h after IFO injection. Inin vitro assays, bladder smooth muscle preparations were kept in saline solution aerated with 95% O2 - 5% CO2, pH 7.4 and at 37 ⁰ C for isometric muscle contractions record the depolarizing solutions of KCl and carbachol (CCh). For the record of intravesical pressure (IVP) by continuous cystometrogram (CC), laparotomy was performed and a polyethylene catheter attached to the bladder and exteriorized through the abdominal region was connected to a system of continuous infusion of saline (0.04mL/min) and a pressure transducer coupled to an acquisition system biological signals. In animals treated with AMF,BWW was reduced by 83% when compared with IFO-injected mice. L-ARG and DIAZ did not preventIFO-induced BWW effect (1.1% and 11.4%, respectively). Macroscopic and microscopic criteria were significantly reduced in AMF injected mice versus IFO group. L-ARG and DIAZ failed to prevent such criteria in comparison to IFO group. IFO decreased bladder strips contractility response to CCh versus control group (1.36 ± 0.24 Vs 0.18 ± 0.02 g force / mg of dry tissue, p <0.01). AMF prevented the IFO-related decrease in contractility response (1.47 ± 0.16 g force / mg of dry tissue, p <0.01). L-ARG and DIAZ did not alter IFO effect bladder contractility (0.6 ± 0.08 and 0.79 ± 0.12 g force / mg dry tissue, respectively, p <0.01 compared to saline control). In CC analysis, AMF reversed the increased voiding frequency (VF) caused by IFO (18 Vs 5.6 micturition/15 min, IFO and CTR, respectively, p <0.01. AMF – 6.5 micturition/15min; p <0.01 compared to IFO). The VFs in L-ARG and DIAZ (14.5 and 11.2 micturition/15min, respectively) were significantly different from AMF group, p <0.01. Cystometrography recordings of control and AMF groups showed regular micturition cycles with evident contractions associated with bladder emptying, which as markedly different from IFO-injected animals that presented an irregular trace concerning micturition cycles and no evident contractions associated with the urination event. DIAZ also showed similar patterns to that of IFO. Treatment with ODQ did not alter either the in vitro and in vivo effects on bladder dysfunction promoted by IFO or upon protection by AMF. AMF inhibited IFO-related functional alterations in bladders through multiple processes that probably include NO and KATPs without involvingthe generation of cGMP.